Origins of Political Change – The Case of Late Medieval Guild Revolts - Fabian Wahl (European Historical Economics Society (EHES), 2014)
This study investigates the origins of the guild revolts in late medieval central Europe. At first, using newly compiled city level data, their temporal evolution and spatial distribution is discussed. Afterwards, the paper provides a historical discussion and empirical analysis of their origins. The results show that pre-existing city-level political institutions and location in a large territorial state were important for the emergence of late medieval guild revolts. Furthermore, the agricultural productivity of the region around a city matters in a negative way confirming the role of the late medieval agricultural crisis in the outbreak of the revolts. Other important factors are a city's urban environment and market potential, its degree of autonomy and its commercial, industrial as well as political importance. This suggests that economic change can trigger political changes. I also found evidence for the existence of spatial spillovers from the developments in neighboring cities implying that rational strategic considerations played a role in the spread of the revolts.
Keywords: N44; N94; O10; R11; H11; D72; 330; Late Medieval; Early-Modern Period; Political Institutions; Political Change; Guild Revolts; Cities